(RE) inserção do trabalhador no mercado de trabalho: Análise do Sistema de Acompanhamento de Egressos desenvolvido pelo Serviço Nacional de Aprendizagem Industrial (SENAI) de Campina Grande: 2009 - 2011 - Cabral, Rogério da Silva (2012)
Nowadays one of the problems that afflict the government's authorities is the lack of formal work, which guarantees labor rights through the payment of certain legal obligations, like social security and other welfare. From what can be seen, there are some situations that prevent the formalization of labor, such as increase of automation, replacing workers by a machine, the cyclical crises of capitalism, the fall in consumption patterns, the "aging" of the workers and the lack of professional qualification. This study is an analysis of training, qualification and (re)integration of workers in the formal labor market in the city of Campina Grande, using data collected by the National Service of Industrial Learning (Senai) during the period between the years 2009 to 2011. The methodology adopted is documental analysis and field observations of workers and managers. From the data obtained through the monitoring system developed by Senai was found that workers who held their qualifying in that institution were more able to (re)enter the formal labor market.